(untitled) (ARQUISUR Revista, 2018)
This article reflects on partial results collected during research for a doctoral thesis. Proyectualidad, as a teaching object, should be revised in order to highlight pensamiento proyectual as a less explored dimension of the object. Innovation and creativity as features of pensamiento proyectual can be used to assess some of the foundations of the teaching and evaluation of proyectualidad.